Doing business across cultures: a study in business ethics accommodation - Kwon, Sohyun, author; Geroy, Gary, advisor; Fan, Liang-Shing, committee member; Banning, James H., committee member; McCulloch, Michael, committee member (Colorado State University. Libraries, 2004)
A notion of ethics in the business world has been raised in the past 10 years. Several international efforts to do business ethically in one's own country and with other countries were developed and have needed time to become established. In order to establish them, understanding the ways people perceive and behave in different cultures when doing business with each other is quite an important step. Thus, this study has tried to determine whether managers' perceptions of business ethics are different among other cultures, and to determine whether the managers from external cultures tend to follow a target culture's ethical standards of business behavior or adhere to their own. In addition, the managers' concerns about business ethical practices were examined to learn how the managers express their concerns regarding paying more or less or equal attention to other cultures' business ethical practices. Finally, inappropriate business conduct experiences were examined by asking how managers from the culture use inappropriate business practices when doing business with business partners from other cultures. The study's conclusions focus on the perception and behavior members of two different groups exhibit regarding other cultures' business ethics. Two different groups, Danish (Group A) and Korean (Group B) business people, have the same perceptions regarding other groups of cultures, Groups A, B, and C (Indonesia, Kenya, Angola, Madagascar, Paraguay, Nigeria, and Bangladesh). For the ethics perception difference, members of both groups agree that Group A has the highest business ethical standards, followed by Groups B and C. For the ethics commitment degree, members of Group A and Group B show different behaviors. Group A use a mix between two cultures ethical standards but Group B tend to follow the other culture's ethical standards. For the degree of concern about ethics, both Group A and Group B seem to pay more attention to business ethical standards when doing business with other cultures. For the inappropriate business conduct experience, few individuals from Group A used inappropriate business conduct when doing business with other cultures; however, most members of Group B used inappropriate business conduct when doing business with other cultures, especially with Group C.
Keywords: vocational education